Analisis User Experience Aplikasi Disney+ Hotstar dengan Menggunakan Metode User Experience Questionnaire (UEQ) - Danar Feriano; Nabila Rizky Oktadini; Allsela Meiriza; Putri Eka Sevtiyuni; Pacu Putra (STMIK Budi Darma, 2023)
With the advancement of the times, people have started using apps to fulfill their daily needs, such as reading news, shopping, and watching movies. Disney+ hotstar is a video streaming platform that provides various types of movies. There are 107 people who have used the disney+ hotstar application throughout Indonesia as the subject of this research. The problem identified is why users prefer Netflix to watch videos compared to using the disney+ hotstar app. The purpose of the study was to analyze the user experience while using the disney+ hotstar app using the UEQ method and also to provide recommendations on what can be improved to enhance the user experience. After that, the UEQ tool was used to analyze the information that had been collected. The results show that the attractiveness aspect has a value of 1.72 which is a good value, perspicuity has a value of 1.67, which is an above average value, efficiency has a value of 1.49, which is an above average value; dependability has a value of 1.34, which is an above average value, stimulation has a value of 1.43, which is a good value and novelty has a value of 1.05, which is an above average value.